2011
DOI: 10.1038/sc.2011.66
|View full text |Cite
|
Sign up to set email alerts
|

Mission impossible? Urological management of patients with spinal cord injury during pregnancy: a systematic review

Abstract: Study design: A systematic literature review. Objectives: To systematically assess the existing knowledge about treatment of neurogenic lower urinary tract dysfunction (NLUTD) in pregnant women with traumatic spinal cord injury (SCI), as urologic management of these patients is mandatory, but no guidelines are available. Setting: Paraplegic center in Switzerland. Methods: Studies were identified by electronic search of PubMed and MedLine. Data were pooled and analyzed quantitatively. Results: The evidence leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
1
30
1
6
Order By: Relevance
“…A recent review demonstrated that there are virtually no data about the incidence, severity and management of urological complications in these patients. 21 To get a clearer picture, we collected data from women who were concerned about their urological health and other specific SCI medical problems during their pregnancies. The objective of this study was to identify any medical complications and to describe how women with SCIs dealt with those complications during pregnancy and childbirth in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review demonstrated that there are virtually no data about the incidence, severity and management of urological complications in these patients. 21 To get a clearer picture, we collected data from women who were concerned about their urological health and other specific SCI medical problems during their pregnancies. The objective of this study was to identify any medical complications and to describe how women with SCIs dealt with those complications during pregnancy and childbirth in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Une récente revue de la littérature soulève les difficultés de prise en charge urologique des patientes paraplégiques au cours de la grossesse et notamment le faible niveau de preuve des études, ne permettant pas d'établir de recommandations de pratique [11].…”
Section: Discussionunclassified
“…À l'heure actuelle, dans la littérature seules deux études ont été conçues spécifique-ment pour évaluer la problématique urologique au cours de la grossesse chez les femmes BM [7,10]. L'une d'elles est une revue de la littérature récente menée par Pannek et al [10].…”
Section: Discussionunclassified
“…À l'heure actuelle, dans la littérature seules deux études ont été conçues spécifique-ment pour évaluer la problématique urologique au cours de la grossesse chez les femmes BM [7,10]. L'une d'elles est une revue de la littérature récente menée par Pannek et al [10]. Les auteurs ont rapporté que le niveau de preuve de la plupart des études qui abordent le sujet de la grossesse et des problèmes urinaires chez les BM était faible à cause du faible nombre de femmes BM enceintes incluses dans les études, puis à cause du fait qu'il était éthiquement difficile de concevoir un essai randomisé prospectif au sein de cette population dans un contexte de grossesse, et enfin à cause de l'importance des données manquantes.…”
Section: Discussionunclassified
See 1 more Smart Citation